2020
DOI: 10.3906/sag-1911-86
|View full text |Cite
|
Sign up to set email alerts
|

Value of prognostic scores in antineutrophil cytoplasmic antibody (ANCA) associated vasculitis patients in intensive care unit: a multicenter retrospective cohort study from Turkey

Abstract: Background/aim: There is a need for a scoring system for predicting ICU prognosis of patients with ANCA-associated vasculitis (AAV), but there are limited data on it in the literature. Therefore, we aimed to determine the scores that can estimate the prognosis of patients with AAV during intensive care follow up. Materials and methods: All adult patients admitted to the medical ICUs of 4 reference university hospitals in Turkey due to AAV activation and/or disease/treatment complications in the last 10 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 17 publications
(35 reference statements)
1
15
1
Order By: Relevance
“…In a study that focused on the outcome of rheumatology patients with acute respiratory failure, the in-ICU mortality rate was high (59.8%), and vasculitis was associated with increased mortality (49). Ozdemir et al showed in their study that 5 (25.0%) patients died of respiratory failure, with massive hemoptysis (four patients) and resistant pulmonary edema (one patient) (11). Demiselle et al reported that in-ICU death of five patients (33.0%) was attributed to multiple organ failure likely due to sepsis (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study that focused on the outcome of rheumatology patients with acute respiratory failure, the in-ICU mortality rate was high (59.8%), and vasculitis was associated with increased mortality (49). Ozdemir et al showed in their study that 5 (25.0%) patients died of respiratory failure, with massive hemoptysis (four patients) and resistant pulmonary edema (one patient) (11). Demiselle et al reported that in-ICU death of five patients (33.0%) was attributed to multiple organ failure likely due to sepsis (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, some AAV patients may require intensive care unit (ICU) admission due to life-threatening manifestations at the time of diagnosis, disease flare-up or severe complications due to immunosuppressive therapies (6)(7)(8). AAV is one of the most frequent systemic rheumatic diseases (SRD) in the ICU (9,10) with high mortality ranging from 15.5% to 58.8% (8,11,12). According to researches, the in-ICU mortality is higher among AAV patients compared with other SRD patients (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, this may partly be limited to the level of medical treatment in our center. Importantly, patients with other systemic autoimmune disease such as antineutrophil cytoplasmic antibody (ANCA) associated vasculitis may sometimes require admission to the ICU due to life threatening conditions (31)(32)(33)(34)(35). Compared with patients with SLE, patients with ANCA-associated vasculitis in the ICU were older, with a median age of more than 60 years, and were more common in male.…”
Section: Discussionmentioning
confidence: 99%